2001
DOI: 10.1093/toxsci/62.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Masculinization of Female Mosquitofish in Kraft Mill Effluent-Contaminated Fenholloway River Water Is Associated with Androgen Receptor Agonist Activity

Abstract: Female mosquitofish (Gambusia affinis holbrooki) downstream from Kraft paper mills in Florida display masculinization of the anal fin, an androgen-dependent trait. The current investigation was designed to determine if water contaminated with pulp-mill effluent (PME) from the Fenholloway River in Florida displayed androgenic activity in vitro and to relate this activity to the reproductive status of female mosquitofish taken from this river. We tested water samples for androgenic activity from a reference site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
173
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(178 citation statements)
references
References 40 publications
4
173
1
Order By: Relevance
“…Recently, it was reported that androstenedione was present after a chemical characterization of the effluent from a paper mill plant in Florida (50). Using a number of in vitro receptor binding and gene expression assays, our laboratory in collaboration with others has not found sufficient androstenedione concentration in Fenholloway River water samples to support the reported significant androgenic actions of this effluent, however (15).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, it was reported that androstenedione was present after a chemical characterization of the effluent from a paper mill plant in Florida (50). Using a number of in vitro receptor binding and gene expression assays, our laboratory in collaboration with others has not found sufficient androstenedione concentration in Fenholloway River water samples to support the reported significant androgenic actions of this effluent, however (15).…”
mentioning
confidence: 84%
“…A wide range of chemicals were shown to have an affinity for estrogen receptors from various species (12). In addition to the estrogenic or antiestrogenic nature of chemical contaminants, data are currently available documenting antiandrogenic (8,9), androgenic (13)(14)(15), antiprogestogenic (16), and antithyroidal actions (17)(18)(19). The mechanisms behind these actions appear varied, with receptor binding only one of a number of possible responses.…”
mentioning
confidence: 99%
“…Surface water and sediment samples were collected from the Liuxi, Shijing, and Zhujiang rivers of the Pearl River system in the dry season (December [17][18]2007) and the wet season (September [10][11][12]2008). In total, 15 sampling sites along the three rivers were selected (Fig.…”
Section: Sample Collection and Extractionmentioning
confidence: 99%
“…Male fish feminization in receiving waters has been related to residual natural and synthetic estrogens from municipal STP effluents [8,9]. Effluents from pulp and paper mills displayed androgenic activity in female fish, leading to masculinization or sex reversal of female fish [10,11]. Very recently, screening assays revealed that androgenic activity also exists widely in industrial and hospital wastewaters, municipal STP effluents, and even in surface water in association with estrogen, progesterone, and glucocorticoid receptor activities [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of reports on intersex organisms found in global aquatic ecosystems has raised concerns regarding the occurrence and persistence of steroid hormones in the environment (Safe, 2004;Wise et al, 2011). Several studies have reported the masculinization of freshwater wildlife exposed to androgens in polluted rivers (Howell et al, 1980;Bortone et al, 1989;Parks et al, 2001;Orlando et al, 2004). Furthermore, steroids were identified as pheromones and adversely affect fish behavior even at extremely low concentrations (Kolodziej et al, 2003).…”
Section: Introductionmentioning
confidence: 99%